Kenya, Land Tenure, Agricultural Productivity and the Environment: Suba and Laikipia Districts, 2001 - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
The Land Tenure, Agricultural Productivity and the Environment: Suba and Laikipia Districts, Kenya, 2001 dataset accompanies a study that examines the relationships between the land tenure, agricultural productivity, and the environment in order to provide the necessary policy guidelines to the Government and other stakeholders. The study was carried out in two districts, Suba and Laikipia. It is believed that these two districts provide a wide range of tenure systems, cultural backgrounds and agro-ecological diversities on which reasonable policy conclusions can be made. Specific objectives of this study were: Establish the relationship between security of tenure and agricultural productivity; Identify and establish the link between security of tenure and investment in environmental conservation and soil fertility enhancement and maintenance; Establish the link between tenure system and environmental degradation; and Analyze gender relations, land tenure and productivity. The dataset contains information on household characteristics such as household income, occupation, socioeconomic background, land characteristics such as parcel size, sale of land, security of access to land, and others including environmental degradation, conservation measures, hired labor, livestock ownership, infrastructure, and access to credit. The survey was undertaken in 4 sub-locations per district. These were randomly selected from a cluster of 10 sub-locations in each district. Each of these clusters was expected to have almost the same agro-ecological conditions with a wide range of tenure systems. In each selected cluster, a list of the household heads were compiled. The target respondents were then randomly selected from this list. A total of 40 respondents was randomly selected from each cluster (sub-location).